Management of political risks and its influence on the strategy of organizations in Sudan – Field study on the organizations working in Khartoum state - Elgafari, Mohammed Elnagi (Journal of Economic, Administrative and Legal Sciences, 2021)
Management of political risks and its influence on the strategy of organizations in Sudan.This study, which is considered an exploratory study, aimed at identifying the impact of political variables on the organizations operating in Sudan and how it’s managed by the organization, and by focusing on those working in the Khartoum state. The study stems from the fact that this study is an exploratory study of a previously unexplored field. The study obtains a random sample of 50 companies from the biggest one in Khartoum state, the data has been collected by way of a questionnaire and analysed statistically and logically. The study was conducted with a number of results and recommendations, the most important of which is the impact of the political risks with a ratio of 60%, and the political instability in Sudan negatively influence the Sudanese business organizations with a ratio of 74%. In spite of difficulties facing the government factor (48%) of the sample, which led them to adapted defence Strategies, 48% of the sample has no organizational body to analyzes the environment. Only 28% of the sample get help from an outside consultant. Some of the strategies adopted by Sudanese organization to avoid the risks is distributing the investments (46%) of the sample, 18% of the organization used immoral ways to gain government opportunities. The study recommended analyzing the external environment to overcoming the lack of information. Also, the organisation must avoid the immoral ways to get the government incentives, the difficulties of obtaining data can be solved by a good information system.